Penerapan Technological Pedagogical Content Knowledge (TPACK) dalam Pembelajaran Pendidikan Agama Islam di SDIT Bakti Insani - Wuryan Hutami; Lovandri Dwanda Putra; Iftiani Nabilah Niarna; Nafisa Rahmalia Davi A.; Alya Nada Nauroh; Syafira Aulia (QuranicEdu: Journal of Islamic Education, 2026)
Digital transformation requires Islamic Education (PAI) teachers to possess integrated pedagogical, content, and technological competencies. However, PAI learning is still often conducted in a conventional manner and tends to be less engaging for elementary school students. This study aims to describe the implementation of Technological Pedagogical Content Knowledge (TPACK) in PAI learning at SDIT Bakti Insani as a contextual learning solution in the digital era. The study employed a descriptive qualitative approach through semi-structured interviews with PAI teachers. The findings indicate that TPACK integration is carried out through strengthening content based on an integrated curriculum, pedagogical strategies aligned with students’ characteristics, gradual use of educational technology, as well as teacher collaboration and continuous professional development. In conclusion, TPACK is effective in improving the quality of meaningful, interactive, and relevant PAI learning.